2016
DOI: 10.1016/j.vaccine.2016.03.094
|View full text |Cite
|
Sign up to set email alerts
|

Multiple antigens of Yersinia pestis delivered by live recombinant attenuated Salmonella vaccine strains elicit protective immunity against plague

Abstract: Based on our improved novel Salmonella vaccine delivery platform, we optimized the recombinant attenuated Salmonella Typhimurium vaccine (RASV) χ12094 to deliver multiple Y. pestis antigens. These included LcrV196 (amino acids, 131 to 326), Psn encoded on pYA5383 and F1 encoded in the chromosome, their synthesis did not cause adverse effects on bacterial growth. Oral immunization with χ12094(pYA5383) simultaneously stimulated high antibody titers to LcrV, Psn and F1 in mice and presented complete protection ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…challenge with 5000 CFU (~50 LD 50 ) of Y. pestis CO92. 68 Oral immunization with χ12094(pYA5383) did not caused any deaths or disease symptoms in SCID mice over a 60-day period. 68…”
Section: Live Vectored Plague Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations
“…challenge with 5000 CFU (~50 LD 50 ) of Y. pestis CO92. 68 Oral immunization with χ12094(pYA5383) did not caused any deaths or disease symptoms in SCID mice over a 60-day period. 68…”
Section: Live Vectored Plague Vaccinesmentioning
confidence: 99%
“…104 Thus, combination of multiple antigens was tested to prevent this risk. 68,70,105 Studies have suggested that vaccine efficacy may be different when measuring protection against bubonic or pneumonic plague infection. Th1-skewed and Th17-skewed immune responses from vaccines provide better protection against the pulmonary Y. pestis infection than Th2-skewed responses from subunit vaccine.…”
Section: Efficacy and Safety Of Plague Vaccine Where Is The Cut-off?mentioning
confidence: 99%
See 1 more Smart Citation
“…A key engine to driving SBP structural investigations has been the use of Escherichia coli to produce recombinant SBPs from many genera (Lee et al, 1999;Ilari et al, 2011;McDevitt et al, 2011;Gribenko et al, 2013;Handali et al, 2015), including Yersinia pestis (Shouldice et al, 2005). E. coli has been reliably used to generate recombinant protein that is physiologically relevant and useful for biotechnological applications, namely drug discovery (Lu et al, 2012;Sanapala et al, 2016). E. coli is particularly useful to study the biology of Y. pestis proteins because both E. coli and Y. pestis are Gramnegative organisms that have similar physiologies and utilize similar cellular machinery.…”
Section: Introductionmentioning
confidence: 99%
“…This group further demonstrated that the higher the level of Ag synthesis (which correlated with decreased fitness for the RASV), the more rapid was the induction of immune responses, especially mucosal responses (136). There is much evidence that secretion (119) or surface display of protective Ags on RASVs and other recombinant attenuated bacterial vaccines results in higher immune responses and protective immunity (133,134,(137)(138)(139)(140)(141)(142)(143)(144)(145). Sizemore et al (146) determined that a DphoPQ-attenuated S. Typhimurium strain induced much higher Ab titers against Yersinia pestis Ags F1 and LcrV when these Ags were retained in the cytoplasm rather than when they were secreted.…”
mentioning
confidence: 99%